THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE AND EMPLOYEE SATISFACTION AS AN INTERVENING VARIABLE AT HOTEL GROVE SUITES JAKARTA - Fetty Asmaniati; Nurbaeti Nurbaeti; Ismeth Emier Osman; Elda Nurmalinda (Universitas Islam Lamongan, 2023)
This research aims to formulate an accurate digital marketing strategy that Camira Kitchen can implement for business development post-Covid-19 pandemic. This research method uses descriptive qualitative method with a case study approach. The data analysis technique uses SWOT analysis. The result showed that the company could implement the most accurate strategy, the market penetration strategy, which is to improve product taste, company services, and content quality to resolve the market competition. This strategy focuses on developing the company’s Instagram by uploading educational content about how to make products, pack products, company’s service, and improve the quality of photos or videos. This strategy is expected to reach the engagement stage until the purchasing decision stage